The New Orleans Sniper: A Phenomenological Case Study of Constituting the Other - Waksler, Frances Chaput (Hamilton Books, 2010)
On January 7, 1973, shots were fired from Howard Johnson's Motel in New Orleans, LA. Six were killed, ten wounded. After the first sniper was killed, the search continued for others. A thorough police investigation, however, concluded that there had been only one —- whose body was found on the motel roof. How did the idea of multiple snipers emerge? How was it decided that there had been only one after all? More generally, how does anyone come to a decision about the existence or nonexistence of another person? In prose both analytic and engaging, Waksler traces the course of this event and the claims and counterclaims made in the search to explain it. Please visit Frances Chaput Waksler's website for additional information regarding her biography, publications, and more: www.franceswaksler.com.